The Effect of Personality Value Practice of Principals toward Attitude, Discipline, Qualities and Communications of Work - Muhammad Asri; Lokman Bin Mohd Tahir (Journal of Education and Learning (EduLearn), 2015)
This study aims to identify the effect of personality value practice of principals toward work attitude, work discipline, work quality and work communication of teachers in senior high schools such as public senior high schools (SMA), vocational senior high schools (SMK), religion senior high schools (MAN) in Makassar city, South Sulawesi province of Indonesia. The sample consisted of 295 teachers. It used random sampling method. The study used a questionnaire to collect data. Data were analyzed by the statistical inference of linear regression to test the hypotheses. Cronbach's alpha of the questionnaire is 0.879. The results showed a strong effect of personality values of principals toward work attitude, work quality and work communication of teachers at schools. While, personality value of principals have moderate influence on teachers’ work discipline.